Life at the crossroads: the nuclear LINC complex and vascular mechanotransduction - Bougaran, Pauline; Bautch, Victoria L. (Frontiers in Physiology, 2024)
Vascular endothelial cells line the inner surface of all blood vessels, where they are exposed to polarized mechanical forces throughout their lifespan. Both basal substrate interactions and apical blood flow-induced shear stress regulate blood vessel development, remodeling, and maintenance of vascular homeostasis. Disruption of these interactions cells leads to dysfunction and vascular pathologies, although how forces are sensed and integrated to affect endothelial cell behaviors is incompletely understood. Recently the endothelial cell nucleus has emerged as a prominent forcetransducing organelle that participates in vascular mechanotransduction, via communication to and from cell-cell and cell-matrix junctions. The LINC complex, composed of SUN and nesprin proteins, spans the nuclear membranes and connects the nuclear lamina, the nuclear envelope, and the cytoskeleton. Here we review LINC complex involvement in endothelial cell mechanotransduction, describe unique and overlapping functions of each LINC complex component, and consider emerging evidence that two major SUN proteins, SUN1 and SUN2, orchestrate a complex interplay that extends outward to cell-cell and cell-matrix junctions and inward to interactions within the nucleus and chromatin. We discuss these findings in relation to vascular pathologies such as Hutchinson-Gilford Progeria syndrome, a premature aging disorder with cardiovascular impairment. More knowledge of LINC complex regulation and function will help to understand how the nucleus participates in endothelial cell force sensing and how dysfunction leads to cardiovascular disease.